Jeopardies of Aversive Leadership: A Conservation of Resources Theory Approach - Fatima, Tasneem; Majeed, Mehwish; Shah, Syed Z. A. (Frontiers in Psychology, 2018)
The research on the dark side of leadership is still in its infancy. We have contributed to this line of research by proposing that work alienation acts as an underlying mechanism through which aversive leadership results in reduced job performance. We further propose that psychological capital acts as an important personal resource that reduces the negative effects of aversive leadership in the form of work alienation. The proposed model gets its support from the conversation of resources theory given by Hobfoll (1981) which suggests that stressful situation like an aversive leadership results in the loss of employee resources as a result of that he/she indulges in work alienation and shows poor job performance to retain back the lost resources. People with better personal resources in the form of psychological capital are better able to cope-up with the aversive leader behavior and make them able to avoid work alienation. It is a time-lagged study. The data for the current study was collected from 321 employees working in the service sector organizations, particularly universities, banks and telecom organizations, through personally administered questionnaires. The results supported the mediation and moderation hypothesis. Limitations and future research along with theoretical and practical implications are given at the end.